Extended GT-STAF Information Indices based on Markov Approximation Models - Barigye, Stephen J.; Marrero-Ponce, Yovani; Alfonso-Reguera, Vitalio; Pérez-Giménez, Facundo (Chemical Physics Letters, 2013)
A series of novel information theory-based molecular parameters derived from the insight of a molecular structure as a chemical communication system were recently presented and usefully employed in QSAR/QSPRs (J. Comp. Chem, 2013, 34, 259; SAR and QSAR in Environ. Res. 2013, 24). This approach permitted the application of Shannon’s source and channel coding entropic measures to a chemical information source comprised of molecular ‘fragments’, using the zero-order Markov approximation model (atom-based approach). This report covers the theoretical aspects of the extensions of this approach to higher-order models, introducing the first, second and generalized-order Markov approximation models.
Keywords: GT-STAF; Markov; QSAR/QSPRs